2021
DOI: 10.1101/2021.07.07.451375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multivalent designed proteins protect against SARS-CoV-2 variants of concern

Abstract: Escape variants of SARS-CoV-2 are threatening to prolong the COVID-19 pandemic. To address this challenge, we developed multivalent protein-based minibinders as potential prophylactic and therapeutic agents. Homotrimers of single minibinders and fusions of three distinct minibinders were designed to geometrically match the SARS-CoV-2 spike (S) trimer architecture and were optimized by cell-free expression and found to exhibit virtually no measurable dissociation upon binding. Cryo-electron microscopy (cryoEM) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…LCB1 was designed specifically against the receptor-binding domain of the SARS-CoV-2/WA1 variant isolated in 2020. As variants emerge, these spike binder proteins may lose their potency if critical binding domains are mutated, necessitating new designs ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCB1 was designed specifically against the receptor-binding domain of the SARS-CoV-2/WA1 variant isolated in 2020. As variants emerge, these spike binder proteins may lose their potency if critical binding domains are mutated, necessitating new designs ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from a controlled human cohort of COVID-19 patients support the physiological relevance of the findings in organoids. The remarkable tropism observed in these organoids, their ability to reveal physiologically relevant injury, and their accessibility to genome editing, together with the availability of urine samples from patients for proteomic analysis, combine to establish a powerful system for studying COVID-19 renal pathophysiology and developing therapeutics ( 19 , 22 , 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, several vaccines for SARS-CoV-2 have been put on the market. However, the virus is prone to mutation and its genome is characterised by high diversity and frequent recombination, leading to weak protective power and insufficient duration of protection 7 . Additionally, frequent cross-species transmission further emphasises the importance of fundamental preventive and therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the SARS-CoV-2 pseudovirus neutralization assays showed that the binding enhancement observed in the trimeric assembly translated into increased neutralization ability when compared to both the genetically conjugated and GCE-conjugated dimers. Similarly, a recent study using designed RBD mini-binders also showed that SARS-CoV-2 neutralization was improved by trimerization, and that the topology of trimerization mattered, although, in that case, the topologies tested were all limited to genetic linkages through the N and C termini ( 34 ).…”
Section: Discussionmentioning
confidence: 94%